A diversidade linguística no contexto escolar - Souza, Antonio Escandiel de; Pautz, Sílvia (Linguagens & Cidadania, 2017)
This article is a result of a developing project by Universidade de Cruz Alta. The methodology used consists of reading and application of questionnaires and interviews with students of primary and high schools from Panambi. The previous outcomes suggest that the reason of some discrimination in the classroom is due to the student’s speaking way and some teachers don’t realize yet the enormous linguistic diversity in our country. In this sense, many traditional teachers discriminate their students because according to them, the pupils don’t know the Portuguese language. In fact these professionals don’t notice the linguistic diversity of Brazil.